ORGANIZATION OF DIRECT MEMORY ACCESS (Intent Research Scientific Journal, 2024)
The work considers the mode of direct access to memory with the provision of communication between the PDP controller and the microcomputer memory. The PDP controller is shown for inputting data from the VU in the "Cycle Capture" mode and disconnecting the processor from the system interface buses.